Malnutrition and poor oral health status are major risks among primary school children at Lasbela, Balochistan, Pakistan - Muhammad Ayaz Mustufa; Abdul Karim Jamali; Ifra Sameen; Fateh Muhammad Burfat; Mir Yousaf Baloch; Abdul Hameed Baloch; Ghulam Rasool Baloch; Shazia Kulsoom Lashari; Sobiya Mohiuddin Ayaz; Muhammad Younus Baloch (BMC, 2017)
Abstract Background This survey was focusing on health and oral hygiene status of primary school children at Lasbela district considering the comparatively less developed and socio demographically deprived part of the Country. Methods A cross sectional survey was conducted to determine the health status of primary school children in seven tehseels of district Lasbela, Balochistan after applying proportionate sampling technique from March 2015 to July 2015. Field teams visited assigned schools to screen children and collect health related data on predesigned and pre coded proforma. Results Out of 200 schools, 196 schools found opened, while 2% of schools (04) remained closed. A total of 6363 students were clinically screened. About 45% of the school children had normal body mass index (BMI) and rest were falling in different categories of malnutrition. More than 19% had ear, nose and throat (ENT) problems and around 19% presented with clinical anemia. Less than 50% of children had scar of BCG vaccination and 4% informed about use of gutka/supari chewing (smokeless tobacco use). Conclusion In conclusion, we estimated high prevalence of malnutrition, poor oral health including smokeless tobacco use, and low BCG coverage among primary school children at Lasbela. Current scenario suggests immediate and contextually focused interventions to confine existing public health risks and avoid future burden of disease.